The structure and the weighted average price of working capital - M. A. Pertseva (Путеводитель предпринимателя, 2020)
The problems of developing models and methods of estimating the quality of the structure of the weighted average cost of capital and working capital of the industrial enterprise is considered, that is very important for optimal management of investments in fixed and working capital in terms of price heterogeneity, different conditions of access and market volumes source equity and debt financing.